An integrative in silico approach to the structure of Omp33-36 in Acinetobacter baumannii. (February 2018) - Jahangiri, Abolfazl; Rasooli, Iraj; Owlia, Parviz; Fooladi, Abbas Ali Imani; Salimian, Jafar
Graphical abstract: Highlights: Topology, secondary and tertiary structures of Omp33-36 were confirmed. An integrative in silico approach was invoked to predict Omp33-36 structure. Omp33-36 shared structural similarity to CymA in Klebsiella oxytoca . About 15 resides at the N -terminus of CymA does not exist in Omp33-36. Porin function of Omp33-36 could be justified by the introduced model. Abstract: Omp33-36 in A. baumannii, a bacterium causing serious nosocomial infections, is a virulence factor associated with the pathogen metabolic fitness as well as its adherence and invasion to human epithelial cells. This protein is also involved in interaction of the bacteria with host cells by binding to fibronectin. Moreover, Omp33-36 renders cytotoxicity to A. baumannii in addition to inducing apoptosis and modulation of autophagy. In the present study, an integrated strategy is launched to pierce into the 3D structure of Omp33-36 protein. The signal peptide within the sequence was determined, then, topology as well as secondary and tertiary structures of the protein were predicted. The mature protein assigned as a 14-stranded barrel in which residues 1–19 is removed as signal peptide. The obtained 3D models were evaluated in terms of quality; and then, served as queries to find similar protein structures. The hits were analyzed regarding topology among which 14-stranded were considered. The most qualified model was refined and then its sequence aligned to its counterpart similar structure protein (CymA from Klebsiella oxytoca ). The determined structure of Omp33-36 could justify its porin function and carbapenem-resistance associated with the loss of this protein.